Mulheres, arte e domesticidade: entre a arte feminista e o Dicionário do Lar - Silvia Amelia Nogueira de Souza (2011)
This master thesis focuses the linkages between fine arts, women, domesticity and feminism. It builds an analyses of a women's guide, the Dicionário do Lar; and discusses the 70's feminist fine arts, addressing an exposurore of 72's Womanhouse, amongst another works ofthe early feminist fine art. This study presents an unprecedent analysis of the Dicionário do Lar which lists the attributes of women's model, as a source paradigm to guide the analysis of the categorial foundations of feminist fine arts.